2009
DOI: 10.1016/j.exger.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves functional post-ischemic recovery in senescent heart

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. and eNOS myocardial contents. ACCEPTED MANUSCRIPT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
2
24
0
2
Order By: Relevance
“…Regulation of HSP70 expression is related to exercise intensity or type. Data from training studies in human or rodent are reporting increased HSP70 content of myocardium (Thorp et al 2007;Marini et al 2007;Le Page et al 2009). A single bout of exercise or training increases production of HSP70, which protects cells against various stressinduced damage or apoptosis in several tissues (Siu et al 2004;Mikami et al 2004;Antunes-Neto et al 2006).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Regulation of HSP70 expression is related to exercise intensity or type. Data from training studies in human or rodent are reporting increased HSP70 content of myocardium (Thorp et al 2007;Marini et al 2007;Le Page et al 2009). A single bout of exercise or training increases production of HSP70, which protects cells against various stressinduced damage or apoptosis in several tissues (Siu et al 2004;Mikami et al 2004;Antunes-Neto et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Exercise training accelerated the exhaustive exercise-induced LV apoptosis, at least in part, through the mitochondria-mediated regulations. The induction of HSP70 may be beneWcial against ischemic cardiac diseases (Le Page et al 2009) and for cardioprotection by exercise treatment (Kavazis et al 2008;Tupling et al 2008). Regulation of HSP70 expression is related to exercise intensity or type.…”
Section: Discussionmentioning
confidence: 99%
“…At the opposite, physical exercise has been implicated with positive effects on cardiovascular system, such as protective effects against ischemic events (Le Page et al 2009;Kruk 2007) and increase on antioxidant enzymes (Chaves et al 2006) and the use of ND could be related to a loss of the beneficial effects of physical exercise (Chaves et al 2006;Cunha et al 2005).…”
Section: Introductionmentioning
confidence: 97%
“…There are epidemiological and clinical data supporting the hypothesis that poor quality of diet during developmental period increases the risk for several diseases including cardiovascular diseases 26,27 . In the opposite direction, hefty evidences have demonstrated that physical exercise counteracts the deleterious effect of several metabolic and cardiovascular diseases 14,28 . The Developmental Origins of Health and Disease hypothesis considers that nutritional insult between development and early ages induces fetus or newborn adaptation in response to the signals in the intrauterine environment, resulting in adjustments to support immediate survival and improve success in an adverse postnatal environment 29 .…”
Section: Discussionmentioning
confidence: 99%